2022
DOI: 10.1038/s41598-022-16553-0
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the oomycete pathogen Saprolegnia parasitica in aquaculture and the environment

Abstract: Saprolegnia parasitica causes saprolegniosis, a disease responsible for significant economic losses in aquaculture and declines of fish populations in the wild, but the knowledge of its distribution and prevalence in the environment is limited. We developed a fast, sensitive and specific S. parasitica droplet digital PCR (ddPCR) assay and demonstrated its applicability for the detection and quantification of the pathogen in environmental samples: swab DNA collected from the host (trout skin, surface of eggs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Different environmental stressors in the studied farm rendered tilapia more susceptible to S. parasitica infections. Stressful situations can compromise the host's immune system and enhance its vulnerability to saprolegniasis (Pavić et al 2022). Saprolegniasis outbreaks were reported in numerous Egyptian tilapia farms (El-Ashram et al 2007;Zahran et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Different environmental stressors in the studied farm rendered tilapia more susceptible to S. parasitica infections. Stressful situations can compromise the host's immune system and enhance its vulnerability to saprolegniasis (Pavić et al 2022). Saprolegniasis outbreaks were reported in numerous Egyptian tilapia farms (El-Ashram et al 2007;Zahran et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, ddPCR stands apart from conventional PCR and qPCR as it utilizes a specialized instrument to create and analyse the droplets, which allows for the more precise quantification of the targeted nucleic acid. In terms of fish health, the ddPCR assay has shown success in detecting different piscine pathogens, including viruses, bacteria and parasites (Jia et al, 2017; Jiang et al, 2022; Lewin et al, 2020; Lin et al, 2020; Orioles et al, 2022; Pavić et al, 2022; Wang et al, 2021). Furthermore, previous studies have reported that ddPCR is more sensitive than TaqMan qPCR in detecting the infectious spleen and kidney necrosis virus (ISKNV) in tilapia, with a detection limit of 1.4 copies/μL for ddPCR and 34 copies/μL for TaqMan qPCR, respectively (Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The small difference in comparison to our study could be due different approaches in the assay, such as a different quencher at probe, PCR reaction mix and PCR cycler. It seems that the S. parasitica qPCR assay used here has a lower detection limit than that reported for qPCR assays based on amplification of the A. astaci ITS region, which have ranged from 50 fg to 160 fg [27,28] or ddPCR assay of S. parasitica, which was determined as 14 fg gDNA [25]. The genome of A. astaci is larger than that of S. parasitica, and multiple ITS regions are present in different species of oomycetes, varying in number even within the species [29], so comparison between different oomycete species and strains is difficult as such.…”
Section: Discussionmentioning
confidence: 74%
“…Furthermore, to our knowledge, the diagnostic recognition of S. parasitica from fish with PCR has not been published before this study. However, digital droplet PCR (ddPCR) assay to quantify S. parasitica from water and fish samples was recently published [25] and further comparison in vivo of these methods would be interesting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation